The Role of Entrepreneurial Personality Mediation and Technological Competencies Moderation in Determining Entrepreneurial Intentions in Vocational Education - Mutohhari, Farid; Triyono, Mochamad Bruri; Sudira, Putu; Nurtanto, Muhammad; Kholifah, Nur (Journal of Technical Education and Training, 2023)
The importance of intention in producing graduates who are ready for entrepreneurship has not been addressed in depth by vocational education. The lack of entrepreneurial personality that is supported by technological competence is the main problem. In addition, low social and psychological capital is a consequence of these problems. This study examines the determination of the influence of social and psychological capital, and entrepreneurial personality on entrepreneurial intentions. In addition, the entrepreneurial personality is tested for its role as a mediator and the moderating effect of technological competence is tested, which includes technological capacity and capability. Ex-post facto research involving 647 participants. Data were collected through a questionnaire with a Likert scale of 1-5. SEM analysis was used to test the direct effect based on the path coefficient and the mediation and moderating effect based on the bootstrap results. Social and psychological capital, and entrepreneurial personality have a significant effect on entrepreneurial intentions. Entrepreneurial personality plays a significant role in mediating the effect of social capital, but not on the influence of psychological capital. Meanwhile, capacity and capability only play a significant role in moderating the influence of social capital, even though technological capabilities are able to significantly moderate entrepreneurial personality. These results indicate the importance of social and psychological capital, and entrepreneurial personality as an important foundation for the formation of entrepreneurial intentions in vocational education students. On the other hand, technological competence is very important in strengthening social capital to stimulate the growth of entrepreneurial intentions.